PERBANDINGAN HASIL BELAJAR STATISTIK ANTARA MAHASISWA YANG MENGIKUTI PROSES PERKULIAHAN STATISTIK KONVENSIONAL DENGAN MAHASISWA YANG MENGIKUTI PROSES PERKULIAHAN STATISTIK PHRKK (PERUMUSAN MASALAH, HIPOTESIS, RUMUS, KRITERIA DAN KESIMPULAN) PADA MATERI - Hubertus A. Jehata (PGSD UNIKA SANTU PAULUS RUTENG, 2020)
Abstract: The problem of research is many college students from the faculty of Primary School Teacher Education of STKIP Santu Paulus College have difficulty diunderstanding and doing the compartive research for dependent sample. This problem motivates the researcher to do this research. That is why, the aim of this research is to compare the study result between the college student who attend the conventional class and the college student who attend the PHRKK for subject matter Dependent sample. This research is comparation model. The respondens of this research is the college student of Primary School Teacher Education of STKIP Santu Paulus College. The instrument of this research is test. The data analysis which is being used in this research is t sample.This research shows the counting t is higher than t tabel. T counting is 5,826 is higher than t tabel 1,688. It means there is different study result between the college student who attend the conventional class and the college student who attend the PHRKK. Furhtermore, this different shows in average of the the result study of conventional study which is 67,08 comparing to average college student PHRKK which is 68,39., the counting t is higher than t tabel. T counting is 5,826 is higher than t tabel 1,688. It means there is different study result between the college student who attend the conventional class and the college student who attend the PHRKK class on the topic of Uji Komparasi Sampel Dependent.